2022
DOI: 10.3390/ijms231911094
|View full text |Cite
|
Sign up to set email alerts
|

Role of RNAIII in Resistance to Antibiotics and Antimicrobial Agents in Staphylococcus epidermidis Biofilms

Abstract: Staphylococcus epidermidis is a known opportunistic pathogen and is one of the leading causes of chronic biofilm-associated infections. Biofilm formation is considered as a main strategy to resist antibiotic treatment and help bacteria escape from the human immune system. Understanding the complex mechanisms in biofilm formation can help find new ways to treat resistant strains and lower the prevalence of nosocomial infections. In order to examine the role of RNAIII regulated by the agr quorum sensing system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Minich et al, found that oxacillin at the 1/2× MIC concentration decreased the relative mRNA expression of icaA in the biofilm-producing strain S. epidermidis RP62A comparison to untreated control ( p < 0.01). In the presence of oxacillin (1/2× MIC) and vanillin (1/20× MIC), icaA expression decreased by 55% ( P < 0.0001), highlighting the advantages of combinatorial strategy in repressing the biofilm determinant genes [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Minich et al, found that oxacillin at the 1/2× MIC concentration decreased the relative mRNA expression of icaA in the biofilm-producing strain S. epidermidis RP62A comparison to untreated control ( p < 0.01). In the presence of oxacillin (1/2× MIC) and vanillin (1/20× MIC), icaA expression decreased by 55% ( P < 0.0001), highlighting the advantages of combinatorial strategy in repressing the biofilm determinant genes [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important clinical consideration is to determine the strain susceptibility and optimal form of treatment, otherwise, the patient's condition may worsen [102]. In addition, limitations and challenges should be carefully weighed.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, RNAIII inhibitory peptides (RIPs) have shown inhibitory effects on agr and biofilm. It is believed that targeting this molecule will diminish the production of some virulence factors and toxins [101,102]. Similarly, based on the inhibition of agr of another subgroup [103], natural and synthetic AIPs may be introduced as potential inhibitors.…”
Section: Anti-qs Approachesmentioning
confidence: 99%